ANALYSIS OF THE EFFECTIVENESS OF GOLD AND SUKUK AS A HEDGE - Windi Wahyuni Simanjuntak; Darwis Harahap; Abdul Nasser Hasibuan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze and compare the effectiveness of gold and sukuk as hedging instruments. Using historical data for the period 2014-2023, the study was conducted using a quantitative methodology through granger causality test analysis, One way ANOVA, Paired sample t-test. The results of the study show that gold has a higher effectiveness as a hedging instrument, as evidenced by a correlation of 0.72 (compared to sukuk 0.31), beta 1.25 (compared to sukuk 0.45), and Sharpe Ratio 1.85 (compared to sukuk 1.12). In periods of high inflation such as 2014 (8.36%) and 2022 (5.95%), gold showed a faster and more proportional response than sukuk. This study concludes that gold is a more effective hedging instrument than sukuk in the context of the Islamic financial market.